Effect of Sex Differences on the Association Between Stroke Risk and Left Atrial Anatomy or Mechanics in Patients With Atrial Fibrillation - Yoshida, Kuniko; Obokata, Masaru; Kurosawa, Koji; Sorimachi, Hidemi; Kurabayashi, Masahiko; Negishi, Kazuaki (Circulation. Cardiovascular imaging, 2016)
Embolic stroke in atrial fibrillation is more prevalent in women than in men, yet the basis for this difference remains unclear. This study seeks to elucidate whether there are any sex differences in the relationships between stroke risk (CHADS score, CHA DS -VASc score without a sex category, and estimated stroke rate) and left atrial (LA) anatomy or mechanics in patients with atrial fibrillation. LA emptying fraction and global peak atrial longitudinal strain were assessed in 414 subjects with paroxysmal or persistent atrial fibrillation (156 women and 258 men). Linear regression models with an interaction term were performed to test the effect of sex difference on associations between the embolic risk and LA function or anatomy. Sensitivity analyses were performed in 228 age, heart rate, and rhythm-matched subjects (114 women and men). Women were older and had larger LA volumes and lower LA mechanics than men. Significant negative association between the CHADS score and LA emptying fraction was only demonstrated in women with a significant interaction between sexes. Similar significant interactions were found in global peak atrial longitudinal strain but not in LA volume. These findings were corroborated in the comparisons against CHA DS -VASc score without a sex category and the estimated stroke rate. Sensitivity analyses in the matched subgroup also confirmed the robustness of these sex differences in LA emptying fraction, but less so in global peak atrial longitudinal strain. Significant sex interactions on the association between global LA function and risk stratification schemes exist, which may be a reason for the higher prevalence of embolic stroke in women.